Penyuluhan Kesehatan dan Promosi Kesehatan: Sebuah Tinjauan Konseptual - I Gede Mahatma Yuda Bakti (STIKes Surya Global Yogyakarta, 2023)
Background : Generally, health promotion aims to improve public health level. It could also be improved through health extension. In other words, health promotion and extensions are needed to improve public health. Unfortunately, in the health promotion literature, health extension has a narrower meaning compared to health promotion. This article provides an in-depth discussions of both terminologies (health extension and health promotion), and their connections. It also proposes that concepts of health extension and health promotion have identical gist.Methods : This research used qualitative approach. Collecting data was employed by desk research. Data was obtained from book, journal, article, regulations, etc. The research analysis utilized content analysis. Results : Health extension was seen only as an information sharing effort, while health promotion carried a wider definition. On the other hand, some people actually consider health promotion as a health information activity. The concepts have much in common. At least this research identified five similar concepts, namely: (1) education type, (2) orientation, (3) objective, (4) target, and (5) ways.Conclusion : The concept of health extension has much in common with the concept of health promotion. Hence, the definition of health extension and health promotion can be interpreted as having the same meaning